Debt and Discipline: Neoliberal Political Economy and the Working Classes - Mahmud, Tayyab (2012)
Over the last three decades, neoliberal restructuring of the economy created a symbiosis of debt and discipline. New legal regimes and strategic use of monetary policy displaced Keynesian welfare, facilitated financialization of the economy, broke the power of organized labor, and expanded debt to sustain aggregate demand. Public laws and policies created a field of possibility within which financial markets extended their reach and brought ever-increasing sections of the working classes and the marginalized within the ambit of the credit economy. Reordered public policies and new norms of personal responsibility demarcated the horizon within which the economically vulnerable pursued strategies of economic survival and security. Neoliberalism deployed refashioned concepts of individual responsibility and human capital to facilitate assemblage of subjects who would engage the financialized economy as risk-taking entrepreneurs. Faced with restructured labor markets, wage pressures, and shrinking welfare, working classes found themselves with little choice but to pay for their basic needs through debt. Engulfment in debt, in turn, induced self-discipline and conformity with the logic of the financialized economy and precarious labor markets. This ensemble sutured debt with discipline